2016
DOI: 10.1188/16.cjon.504-509
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Cognitive Training for Chemotherapy-Related Cognitive Impairment in Breast Cancer Survivors

Abstract: This review suggests that computer-based cognitive training may enhance cognitive function in BCS with chemotherapy-related cognitive impairment. Oncology nurses are in a unique position to support BCS experiencing chemotherapy-related cognitive impairment. In addition to acknowledging BCS' concerns, screening for other potential factors, and providing education on healthy living, nurses may suggest computer-based cognitive training as an approach to managing chemotherapy-related cognitive impairment. Future r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…At the same time, there are many adverse reactions, which brings great pain to patients [ 3 ]. Studies have shown that chemotherapy will cause not only leukocytosis, nausea, vomiting, loss of appetite, bone marrow suppression, hair loss, and so on, but also severe cognitive decline [ 4 ]. Chemotherapy-related cognitive impairment [ 5 ] (chemotherapy-related cognitive impairment, CRCI), also known as chemotherapy brain (chemobrain) or chemotherapy fog (chemofog), is refered to the memory of patients with malignant tumors during or after chemotherapy and the decline of cognitive functions such as power, executive ability, language ability, reasoning ability, and visual space ability [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there are many adverse reactions, which brings great pain to patients [ 3 ]. Studies have shown that chemotherapy will cause not only leukocytosis, nausea, vomiting, loss of appetite, bone marrow suppression, hair loss, and so on, but also severe cognitive decline [ 4 ]. Chemotherapy-related cognitive impairment [ 5 ] (chemotherapy-related cognitive impairment, CRCI), also known as chemotherapy brain (chemobrain) or chemotherapy fog (chemofog), is refered to the memory of patients with malignant tumors during or after chemotherapy and the decline of cognitive functions such as power, executive ability, language ability, reasoning ability, and visual space ability [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data from the ACTIVE Study indicate that cognitive training, specifically SOP training, helps older adults to age better cognitively, even 10 years after receipt of training [ 7 ]. Since this intervention works well in older adults [ 8 ], such targeted cognitive training may be of value for older breast cancer survivors (BCS) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer survivors (BCS) have a high incidence of impairment on neurocognitive tests of SOP [ 10 , 11 ]. Even subtle SOP deficits can disrupt other cognitive domains such as memory and attention, thus impeding everyday functioning at work and home [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a relationship has been observed between emotional well-being (anxiety and depression) and the severity of cognitive alterations in these patients. Therefore, a transdiagnostic intervention can be useful to improve their emotional state and cognitive performance [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Several types of interventions, from pharmacological treatment to physical activity, have been developed to reduce cognitive impairment in cancer patients [3]. Among psychological interventions, cognitive behavioral therapy and cognitive training have shown positive results, although studies on these interventions have been carried out with limited samples of patients or without a control group [8][9][10][11][12]. However, since both anxiety and depression are related to cognitive impairment in cancer patients, a transdiagnostic intervention such as the Unified Protocol (UP) may be effective in reducing the presence of symptoms of cognitive impairment in these patients [13][14][15][16].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%